Complete diphallia - Our technique to avoid complications - Vidyanand Deshpande (Wolters Kluwer Medknow Publications, 2020)
Diphallia is a rare congenital anomaly with the incidence of 1 in 5-6 million live births. We are reporting a case of complete diphallia associated with accessory scrotum and undescended testis in a 2-year-old boy. We did amputation of the left phallus, urethral end-to-side anastomosis between the spatulated end of proximal left penile urethra and side of proximal part of right penile urethra, excision of accessory scrotum, and left-sided orchidopexy. Avoiding dissection in the posterior urethra leads to an acceptable outcome.